Evaluation of Enterococcus faecium NRRL B-2354 as a potential surrogate of Salmonella in packaged paprika, white pepper and cumin powder during radio frequency heating. (February 2020) - Ozturk, Samet; Kong, Fanbin; Singh, Rakesh K.
Abstract: Salmonella contamination of various seasonings and spices has occurred in the last decade. Radio frequency (RF) heating has been shown to be a potential alternative inactivation method for pathogens in low moisture foods (LMF), including spices and vegetable powders. This study aimed to (1) determine the thermal resistance (D and z values) of Salmonella and Enterococcus faecium (E. faecium) NRRL B-2354 as a promising surrogate for thermal validation studies using paprika, white pepper, and cumin powders, and (2) evaluate the efficacy of RF heating on the inactivation of both microorganisms in packaged samples. Samples with initial water activity levels ( a w, 25 ° C ) of 0.45 ± 0.05 were inoculated with Salmonella cocktail ( S . Typhimurium, S . Agona, S . Montevideo, and S . Tennessee) and E . faecium NRRL B-2354 at approximately 8.5 log CFU/g. Inoculated samples were loaded in aluminum test cells and subjected to isothermal treatment in a water bath at 70, 75 and 80 °C. Samples (20 g) were also sealed in small polystyrene petri dishes and subjected to RF heating in a 27.12-MHz, 6-kW pilot scale RF unit with 105 mm electrode gap until the temperature at the geometric center reached 80 °C. The survival of both bacteria was enumerated and converted to log CFU per gram. The change in color of RF heated samples was also evaluated to assess the impact of RF heating on the product quality. Results showed that the thermal resistance of E . faecium at inactivation temperatures is higher than Salmonella in all three spices. Additionally, both microorganisms showed less thermal resistance in paprika than white pepper and cumin powder. The D 80 ° C values of Salmonella and E . faecium were determined to be 1.21 and 1.82 min in paprika, 2.85 and 5.27 min in white pepper, and 4.47 and 9.53 min in cumin powder, respectively. Results also showed that E . faecium is a suitable surrogate for validation of RF pasteurization of Salmonella in spices and RF heating is an effective method to control the contamination of foodborne pathogens in spices. Highlights: Enterococcus faecium is a valid Salmonella surrogate in paprika, white pepper, and cumin powder. An inoculated pack procedure to validate radio frequency pasteurization of selected spices was developed. Inactivation kinetics of both Salmonella and surrogate were determined at 70, 75 and 80 °C. Prediction curves were determined using obtained thermal resistance values (D and z-values).